Annual report 2017: CGIAR Research Program on Livestock - CGIAR Research Program on Livestock (CGIAR Research Program on Livestock, 2018)
The CGIAR Research Program on Livestock Agri-Food Systems (Livestock CRP) was launched in 2017. The Livestock CRP continues a number of the key lines of research initiated under the first phase Livestock & Fish CRP, but with major changes overall in terms of an expanded mandate to strengthen livestock-mediated resilience in livestock-based systems in addition to the original focus on transforming inclusive livestock- based value chains, and with a new flagship dedicated to the environmental issues associated with livestock production. The CRP works to create a well-nourished, equitable and environmentally healthy world through livestock research for development.